2018
DOI: 10.21919/remef.v13i4.337
|View full text |Cite
|
Sign up to set email alerts
|

Traspaso Depreciación-Inflación en México: Análisis de Precios al Consumidor y Productor

Abstract: This paper analyses the exchange rate pass-through to different price indices in Mexico, placing emphasis on the producer prices subdivisions. A VAR model is implemented for the estimations, using a monthly frequency from January 2004 to November 2016. Subsequently, response impulse functions that help measure the impact of the exchange rate shocks on prices are created. The results show that the pass-through elasticity is low for the consumer and producer prices, but it increases in the most recent period. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…The opposite occurs following depreciation of the exchange rate; in this case, the cost of imported inputs increases, as does inflation, with the result that domestic producers have the chance to increase their margins while real wages may decrease, thereby worsening income distribution (Palley, 2001). Even if recent studies have found that Mexico's exchange rate pass-through to inflation was statistically significant but close to zero, González and Saucedo (2018) showed that pass-through depends on the economic sector [2] and the coefficient increases according to the selected period [3]. To detect these effects of the exchange rate, we include in our FCI the agriculture raw material index as an alternative to the commodity index.…”
Section: Methodsmentioning
confidence: 99%
“…The opposite occurs following depreciation of the exchange rate; in this case, the cost of imported inputs increases, as does inflation, with the result that domestic producers have the chance to increase their margins while real wages may decrease, thereby worsening income distribution (Palley, 2001). Even if recent studies have found that Mexico's exchange rate pass-through to inflation was statistically significant but close to zero, González and Saucedo (2018) showed that pass-through depends on the economic sector [2] and the coefficient increases according to the selected period [3]. To detect these effects of the exchange rate, we include in our FCI the agriculture raw material index as an alternative to the commodity index.…”
Section: Methodsmentioning
confidence: 99%